2024
DOI: 10.3233/jad-240072
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Molecular Interactions Between Human Transferrin and Limonene: Natural Compounds in Alzheimer’s Disease Therapeutics

Mohammed Alrouji,
Sabina Yasmin,
Mohammad Furkan
et al.

Abstract: Background: Neurodegeneration is a term describing an irreversible process of neuronal damage. In recent decades, research efforts have been directed towards deepening our knowledge of numerous neurodegenerative disorders, with a particular focus on conditions such as Alzheimer’s disease (AD). Human transferrin (htf) is a key player in maintaining iron homeostasis within brain cells. Any disturbance in this equilibrium gives rise to the emergence of neurodegenerative diseases and associated pathologies, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Plant-derived compounds, specifically flavonoids like limonene, curcumin, naringin, resveratrol, crocin, and naringenin, have gained significant attention for AD treatment during the past decades due to their promising neuroprotective effects via binding to toxicity, ansferrin, downregulating TNF-α, nitric oxide, and oxidative stress, reducing Aβ protein generation and ROS clearance, hindering proinflammatory cytokines’ production, plus mitochondrial toxicity and cholinergic dysfunction reduction. In this context, multiple studies have investigated the therapeutic potency of SA in AD models. SA administration in AD in vivo models, induced by Aβ (1–42), AlCl 3 , and streptozotocin, demonstrated neuronal cell death reduction, glial cell activation, iNOS expression enhancement, and increased antioxidant enzyme levels leading to memory loss prevention and MAO-A and MAO-B blockade, in addition to an appropriate response to chemical and pathological changes in induced memory and learning impairment. In scopolamine-induced AD models, Lee et al demonstrated SA’s potency to ameliorate both long- and short-term spatial memory deficits as well as avoid memory loss through upregulation of hippocampus synaptic activity and the stimulation of brain-derived neurotrophic factor (BDNF) and tropomyosin receptor kinase B (TrkB) expression.…”
Section: Sinapic Acid’s Mechanisms Of Actionmentioning
confidence: 99%
“…Plant-derived compounds, specifically flavonoids like limonene, curcumin, naringin, resveratrol, crocin, and naringenin, have gained significant attention for AD treatment during the past decades due to their promising neuroprotective effects via binding to toxicity, ansferrin, downregulating TNF-α, nitric oxide, and oxidative stress, reducing Aβ protein generation and ROS clearance, hindering proinflammatory cytokines’ production, plus mitochondrial toxicity and cholinergic dysfunction reduction. In this context, multiple studies have investigated the therapeutic potency of SA in AD models. SA administration in AD in vivo models, induced by Aβ (1–42), AlCl 3 , and streptozotocin, demonstrated neuronal cell death reduction, glial cell activation, iNOS expression enhancement, and increased antioxidant enzyme levels leading to memory loss prevention and MAO-A and MAO-B blockade, in addition to an appropriate response to chemical and pathological changes in induced memory and learning impairment. In scopolamine-induced AD models, Lee et al demonstrated SA’s potency to ameliorate both long- and short-term spatial memory deficits as well as avoid memory loss through upregulation of hippocampus synaptic activity and the stimulation of brain-derived neurotrophic factor (BDNF) and tropomyosin receptor kinase B (TrkB) expression.…”
Section: Sinapic Acid’s Mechanisms Of Actionmentioning
confidence: 99%